CSF1R-related leukoencephalopathy presenting with early apathy, hypoactivity, and cognitive flattening: a case report of a diagnostic challenge - Yang, Wen; Li, Chunli; Zhang, Hongjiang; Zhang, Yangjia (Frontiers in Human Neuroscience, 2026)
Hereditary diffuse leukoencephalopathy with axonal spheroids (HDLS) is a rare autosomal dominant leukodystrophy primarily caused by mutations in the colony-stimulating factor 1 receptor (CSF1R) gene, characterized by progressive cognitive and motor decline. We present a case of a 42-year-old Chinese woman with a rapidly progressive syndrome featuring prominent apathy, cognitive impairment, and hypoactivity. Brain magnetic resonance imaging (MRI) revealed extensive confluent white matter hyperintensities (Fazekas grade 3) predominantly in frontal and parietal lobes, cerebral atrophy, and thinning of the corpus callosum. Comprehensive genetic testing identified a heterozygous missense mutation in the CSF1R gene (c.2342C > T, p.Ala781Val), located within the tyrosine kinase domain, confirming the Diagnosis of HDLS. This case highlights early apathy and hypoactivity as red-flag manifestations of CSF1R-related leukoencephalopathy in a 42-year-old woman with rapidly progressive cognitive decline. The atypical presentation, initially mimicking psychiatric or demyelinating disease, underscores the need to consider CSF1R sequencing when encountering early-onset cognitive or behavioral deterioration with unexplained white-matter changes, thereby facilitating timely diagnosis and genetic counseling.